Evaluating the climate change influence on PV-PCM systems: Year-round numerical simulations for arid, Mediterranean, and oceanic regions - Castillo-Del Barrio, E (Elsevier Ltd, 2025)
This article analyzes the advantages of integrating Phase Change Materials (PCMs) into photovoltaic (PV) systems to improve thermal management and efficiency across different climates. The study conducted extensive finite-volume, time-dependent numerical simulations over an entire year, incorporating realistic atmospheric boundary conditions. It evaluates different types of PCMs and thicknesses for arid, Mediterranean, and oceanic climate zones in Chile. By simulating complete annual cycles, the research effectively captures the impacts of day-night variations and seasonal changes on system performance. The findings indicate that incorporating PCMs can significantly increase energy generation by regulating the temperature of solar panels. The optimal PCM selection varies by climate: CaCl 2-6H2O performs best in arid and Mediterranean climates, while CL shows superior performance in oceanic conditions. Annual energy gains reach 5.8% in arid, 7.8% in Mediterranean, and 2.1% in oceanic climates. To assess how future climate changes may affect these systems, the study further analyses climate projections made with the regional climate models from the CORDEX dataset under the RCP8.5 high-emission scenario. Results show that the increments in ambient temperature at the end of the century do not directly correlate with a reduction in annual energy generation. In geographical locations projected to receive increased solar irradiation, as in oceanic climates, energy generation can rise, where systems may experience gains of up to 4.17%. This highlights the importance of considering climate variability when designing and implementing PV-PCM systems. The study provides valuable insights for developing more efficient and sustainable solar energy systems in the context of climate change. © 2025 Elsevier Ltd